2019
DOI: 10.1111/dme.13923
|View full text |Cite
|
Sign up to set email alerts
|

An Irish National Diabetes in Pregnancy Audit: aiming for best outcomes for women with diabetes

Abstract: Aims The purpose of this study was to identify the number of pregnancies affected by pre-gestational diabetes in the Republic of Ireland; to report on pregnancy outcomes and to identify areas for improvement in care delivery and clinical outcomes. Methods Healthcare professionals caring for women with pre-gestational diabetes during pregnancy were invited to participate in this retrospective study. Data pertaining to 185 pregnancies in women attending 15 antenatal centres nationally were collected and analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Pre-gestational diabetes mellitus, type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) are associated with adverse outcomes [1]. Pregnant women with pre-existing diabetes mellitus are at increased risk of congenital malformations [1,2], stillbirth [1,3,4], perinatal mortality [4,5], macrosomia [1,2,4,6], prematurity [4], operative delivery or increased rates of caesarean section (CS) [1,2,4]. However, the quality of the care offered to women with diabetes mellitus can affect the adverse birth outcomes [7] in reducing congenital malformations and stillbirths [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-gestational diabetes mellitus, type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) are associated with adverse outcomes [1]. Pregnant women with pre-existing diabetes mellitus are at increased risk of congenital malformations [1,2], stillbirth [1,3,4], perinatal mortality [4,5], macrosomia [1,2,4,6], prematurity [4], operative delivery or increased rates of caesarean section (CS) [1,2,4]. However, the quality of the care offered to women with diabetes mellitus can affect the adverse birth outcomes [7] in reducing congenital malformations and stillbirths [6].…”
Section: Introductionmentioning
confidence: 99%
“…Providing appropriate clinical care to women with pre-existing diabetes mellitus has a positive impact on pregnancy outcomes. Previous national and international studies found that adverse maternal outcomes are still high for women with pre-existing diabetes mellitus [ 6 , 9 – 11 ]. The goal of the St Vincent Declaration, which was set in 1997, was “achieving pregnancy outcomes in women with diabetes mellitus that approximates that of women with no diabetes mellitus”.…”
Section: Introductionmentioning
confidence: 99%
“… Estimated from Egan et al (Irish pregnancy audit), published in year 2020 20 and applied this estimate to the projected 2018 Irish population (Central Statistics Office [CSO]) 10 …”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy care costs, and specifically those relating to the mode of delivery and neonatal intensive care unit admission were calculated. Resource use was estimated based on the Irish audit 20 and unit costs were identified from a published study 21 …”
Section: Methodsmentioning
confidence: 99%
“…Yet, despite the reach and acceptance of smartphones and the internet, very few studies have used eHealth to supplement traditional PCC [25][26][27][28][29]. Consequently, insufficient PCC coverage and subsequent high rates of adverse maternal/fetal outcomes have remained a persistent public health challenge [9,[38][39][40]. There is therefore a need to leverage smartphone use in the delivery of PCC to women with DM [9,13,41].…”
Section: Introductionmentioning
confidence: 99%